Angiotensin receptor‐neprilysin inhibitor adherence and outcomes in heart failure with reduced ejection fraction - Dong‐Hyuk Cho; Jimi Choi; Jong‐Chan Youn; Mi‐Na Kim; Chan Joo Lee; Jung‐Woo Son; Byung‐Su Yoo (ESC Heart Failure)
Abstract Aims Whether medication adherence to angiotensin receptor‐neprilysin inhibitor (ARNI) in real‐world practice is associated with the reduced risk of all‐cause mortality or hospitalization relative to that with traditional renin–angiotensin system (RAS) blockade remains unclear. This study investigated the influence of medication adherence of ARNI and traditional RAS blockade in heart failure with reduced ejection fraction (HFrEF). Method We conducted a nationwide longitudinal cohort study with patients with HFrEF using data from the Korean National Health Insurance Service data (2017–2021) covering the entire population. A total of 13 483 patients with HFrEF who received ARNI were matched 1:1 with 13 483 patients who received traditional RAS blockade using propensity score matching. The primary outcome was a composite of all‐cause mortality or any hospitalization within one year. Medication adherence was assessed by calculating the proportion of days covered (PDC) relative to total medication prescribed. ARNI and traditional RAS blockade adherence rates were directly compared to analyse their respective associations with the primary outcome. Results Patients in the ARNI group had a lower rate of the primary outcome than those in the traditional RAS blockade group [hazard ratio (HR) 0.78; 95% confidence interval (CI) 0.75–0.81; P < 0.001]. Mean PDC values spanning 1 year were 92.6 ± 14.5% and 90.9 ± 17.7% in the ARNI and RAS blockade groups, respectively (P < 0.001). Among patients with PDC ≥ 80%, the risk of primary outcome was significantly lower in the ARNI group than in the RAS blockade group (HR 0.75; 95% CI 0.72–0.78; P < 0.001) while a risk reduction with ARNI was not observed among patients with PDC < 80% (HR 0.95; 95% CI 0.85–1.05; P = 0.313). The beneficial effect was more pronounced among patients with PDC ≥ 80% than that among patients with PDC < 80% (P for interaction <0.001). Conclusions In a real‐world cohort with HFrEF, ARNI was superior to traditional RAS blockade in reducing the risk of all‐cause mortality and hospitalization. The benefit of ARNI was pronounced among patients with high medication adherence but not among those with low medication adherence, highlighting the importance of adherence to ARNI treatment for HFrEF. Trial Registration PARADE‐HF ClinicalTrials.gov number, NCT05329727.